From Collaboration to Impact: Insights from the DARE UK Community Building programme - Modarres, Najmeh; Waind, Elizabeth; Porter, Katie; Praag, Cassandra Gould Van (International Journal of Population Data Science, 2026)
How can effective community building transform a fragmented Trusted Research Environment (TRE) ecosystem into a connected, standardised one? And how can it elevate the work of data custodians, data scientists and others across the sector, while effectively involving the public? These are some of the questions Data and Analytics Research Environments UK (DARE UK) has explored as it reflects on the development of its community groups. DARE UK’s community groups are collaborative initiatives that bring together partners from across the UK data research landscape to co-create work aligned with the DARE UK mission to establish a safe and collaborative UK network of Trusted Research Environments (TREs). Ahead of the 2026 IPDLN Conference, DARE UK has funded nine Interest Groups -- open-ended groups focused on broad challenges within the scope of the DARE UK programme -- and four Working Groups, which are short-term collaborative efforts typically linked to an Interest Group and focused on specific pieces of work. Six of these groups have now been active for over a year. In this session, we will share case studies from selected active community groups and lessons learned about what it takes to establish a community that can sustain and govern itself. We will discuss the processes involved in developing a charter and code of conduct, defining what a successful community looks like, determining effective funding models based on our experience, and most importantly, meaningfully engaging and involving the public throughout.